Bureaucracy Performance in Public Services in Indonesia - Yusriadi Yusriadi; Umi Farida (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
Bureaucracy is a tool that plays an essential role in the implementation of development in the region. One of the reform agenda is to create a clean government, and free from the practices of corruption, collusion, and nepotism. Performance-based management is the measurement of bureaucratic performance oriented to outcome measurement. The type of research used is literature. The primary data type is data in the form of scientific work related to employee performance, web pages that discuss performance, while corresponding main data are books or other literature that supports and has to do with research. From the results of the study is one of the significant challenges of the public bureaucracy is how to be able to carry out activities effectively and efficiently. By going to a planned change, it will enable a continuous process of change; thus the performance of the government bureaucracy in public service will be more effective and efficient following the expectations and aspirations of the community. The application of good governance with information technology-based can use as a strategy and guidance in providing services to the public.